PERBAIKAN FABRIKASI PALLET BOX DENGAN DESIGN FOR MANUFACTURING (DFM) UNTUK MEMINIMASI BIAYA PRODUKSI DAN KUALITAS - Rohmat Handoko (JURNAL TEKNIK INDUSTRI, 2015)
Improvement of product was needed by every company to increase process efficiency. One of the productimprovement methods is approached by design for manufacturing (DFM). This method is design method to beused to product fabrication considering minimum cost of component, assembly and overhead. PT.Indo Mada Yasathat fabricated pallet box had focus on reducing component and improve production process. Reducingcomponent conducted by eliminate non added value material but still considering quality of the product.Production process can be improved by simplifying the production process. The main goal implementation of ofprocess efficiency is mimimize cost of production and quality. Result of DFM method implementation to produce1 piece of pallet box will minimize the production cost until 20.0 % and minimize quality cost until 27.1%.